The Planetary Collegium: Master Plan for a Distributed Mixed Reality Campus - Anders, Peter (Enquiry The ARCC Journal for Architectural Research, 2008)
This paper describes the design for a Mixed Reality campusfor the Planetary Collegium. The Collegium is an international research network centered at Plymouth, U.K. Its plans call for seven sub-centers, or nodes, to be builtin different parts of the world. These nodes would be linked by shared virtual spaces and digital networks. The paper describes how the Collegium's seeming contradictions (distributed/unified, simulated/physical, local/remote) can be reconciled. The resulting project is a mixed reality that transcends scales from global to local and, ultimately, to the constituent buildings and their digital spaces.